Non-invasive tracking of polarization rotation from speckle contrast using uncorrelated speckle patterns - Roy A.; Singh R.K.; Brundavanam M.M. (My University, 2025)
A technique based on the superposition of two uncorrelated speckle patterns and speckle contrast measurement is proposed and demonstrated to track the polarization rotation of an optical beam behind a scattering layer. One of the superposed speckle patterns is considered as reference, and it is shown that with the help of the reference speckle pattern of a known linear polarization, it is possible to track the polarization rotation behind a scattering layer in a non-invasive manner by measuring the contrast of the resultant speckle pattern. The working principle and the experimental demonstration of the proposed technique are presented, and the experimental results are compared with the theoretically predicted values. The performance of the proposed technique is quantitatively evaluated by determining the rotation of the polarization vector behind the scattering layer for two different cases, namely, polarization rotation by a half-wave plate and sugar solution of different concentrations, and good matches are found between the experimental results and the theoretical prediction. Issues like resolution of tracking the polarization vector rotation and determination of sugar solution concentration are also discussed in the context of the experimental results. The proposed technique can have potential applications in non-invasive sensing and biomedical studies. © 2020 IOP Publishing Ltd.